Social Media and Voter Mobilization during Nigeria’s 2023 General Elections: An Analysis of Political Campaign Strategies and Citizen Engagement - Joseph Ifeoluwa Joy; Mohammed Jibril Nasir; Abdullahi Aliyu Maiwada (Polit Journal Scientific Journal of Politics, 2026)
The 2023 Nigerian General Elections marked a significant turning point in the country’s democratic process, with social media emerging as a central platform for political communication, voter mobilization, and citizen engagement. This paper examines the role of social media in shaping electoral participation during the elections, focusing on how political actors employed digital platforms to disseminate campaign messages, influence public opinion, and mobilize voters. The study further explores the extent to which citizens utilized social media to access political information, participate in political discussions, and engage with electoral processes. The research adopted a qualitative approach based on secondary data analysis. Data were gathered from scholarly journal articles, election observation reports, policy documents, publications from electoral and civil society organizations, media reports, and existing studies on digital political communication and electoral participation in Nigeria. The paper contends that while social media enhanced political awareness and participation, it simultaneously created opportunities for the spread of misinformation, disinformation, political polarization, and digital manipulation that influenced electoral discourse. The paper discovered that social media played a critical role in increasing voter engagement, expanding political participation among previously marginalized groups, and strengthening issue-based political conversations during the election period. However, the effectiveness of these platforms in promoting democratic participation was constrained by challenges relating to information credibility, digital inequalities, and the proliferation of false narratives. The study concludes that social media has become an indispensable instrument of electoral mobilization and democratic engagement in Nigeria.